Field relation and Petrographic study of Tertiary to Quaternary Volcanics in the Northern Benue Trough, Nigeria - Auwalu D; Abubakar U.; Bute S. I.; Daspan R.I.; Diyelmak B.V; Yusuf A.; Tabale R.P; Babanya A.A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The Northern Benue Trough experienced intrusions by Volcanic rocks in the Tertiary to Quaternary Period. Field investigations and analysis of petrographic characteristics were conducted to gain insights into the features of these volcanic plugs and the conditions of their emplacement, eight (8) representative samples of Basalts were thin sectioned and the mineral constituents of the rocks were studied under a Polarized microscope. The Geology of the study area was characterized by Fika Shales of the Pindiga Formation and basaltic plugs. Based on the Petrographic studies, it was observed that the Basaltic rock samples consist of the following average mineralogical compositions; Olivine (30%), Augite (20%), Plagioclase (21%), Iron oxides (19%) and Opaque minerals (10%). Olivine and Augite minerals appeared as phenocryst and surrounded with Opaque minerals which could be Fe or Ti oxides while the plagioclase minerals forming the groundmass of the porphyritic texture. The presence of Augite and Olivine as phenocrysts, while Iron oxides and Plagioclase minerals forming the groundmass in the basalts suggests the presence of magma mixing and possible wall rock interaction during the emplacements of basalts in the study area.